LINEAR GENERATOR PROTOTYPE WITH VERTICAL CONFIGURATION OF SEA WAVE POWER PLANT - Prasetyowati, Ane; Broto, Wisnu; Suryaningsih, Noor (Spektra: Jurnal Fisika dan Aplikasinya, 2021)
There are three types of potential energy sources in the sea: ocean wave energy, tidal energy, and ocean heat energy. Ocean wave energy is a source of considerable energy. Sea waves are an up and down movement of seawater where the energy of sea waves is generated through the effect of air pressure movement due to fluctuations in ocean wave movements. The Ocean Wave Power Plant can use ocean wave energy to convert it into electrical energy. A linear generator is a device that can convert the mechanical energy of linear motion into electrical energy. The application of the ocean wave energy conversion technology, a linear generator system is an electrical machine that functions to convert the mechanical energy of linear motion into electrical energy using the principle of electromagnetic induction. Wave Energy Converter (WEC) technology has been developed with various methods. From the various existing concepts and designs, in general, WEC technology can be classified into three main types, namely Attenuator (horizontal configuration), Point Absorber (linear configuration), Terminator (damping configuration).